Factors Affecting the Sale Price of Bred Heifers and Bred Cows Sold Through Superior Livestock Video Auctions - M. J. Smith; E. D. McCabe; M. E. King; K. E. Fike; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:The objective of the study was to evaluate potential factors influencing the sale price of bred heifers and bred cows sold through video auctions while adjusting for all other factors that significantly influenced prices. Study Description:Descriptive characteristics of lots offered for sale were obtained through a livestock video auction service (Superior Livestock Auction, Fort Worth, TX). Data were available on 1,870 lots of bred heifers sold through video auctions from 2010 through 2018 and 1,237 lots of bred cows sold through video auctions from 2011 through 2018. Two separate multiple regression models were developed to determine the factors influencing the sale price for each. The Bottom Line:Understanding the various factors influencing the sale price of bred heifers and bred cows will allow producers to make more informed investment decisions.
Keywords: bred heifers; bred cows; sale price